Development and Effectiveness of QR Code-Assisted Pop-Up Books to Improve Elementary School Students' Conceptual Understanding - Priatmoko, Sigit; Yanti, Devi Eva; Urifah, Firda Nur; Putri, Alfina Rusydiana (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED), 2024)
This study aims to explain the development procedure and analyze the improvement of understanding of second-grade students of MI Ar Ridlo Malang using Pop-Up Book media assisted by QR Code. This research adopted the ADDIE model, involving 13 second-grade students of MI Ar Ridlo Malang. Data collection was carried out by observation, interviews, questionnaires, and tests. Qualitative data were analyzed using thematic analysis techniques, while quantitative data were analyzed using descriptive statistics techniques. The findings show that the Pop-Up Book product assisted by QR Code obtained a validation score of 99% for the material and 85% for the media, so it can be categorized as "very valid" and worthy of trial. The increase in student understanding was also significant, seen from the average pre-test score of 66.1 which increased to 90 in the post-test. Thus, this media is very valid and effective in improving students' understanding of Pancasila.